1993
DOI: 10.1093/nar/21.10.2349
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of RNA moleculesin vitro

Abstract: A method for RNA amplification in an immobilized medium is described. The medium contains a complete set of nucleotide substrates and purified Q beta replicase, an enzyme capable of exponentially amplifying RNAs under isothermal conditions. RNA amplification in the immobilized medium results in the formation of separate 'colonies', each comprising the progeny of a single RNA molecule (a clone). The colonies were visualized by staining with ethidium bromide, by utilizing radioactive substrates, and by hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…Chetverin and co-workers have introduced and studied RNA colonies that grew and propagated on gels or other solid media provided that RNA replicases and ribonucleoside triphosphates were present [351,377,378]. It has been explicitly noted that such experimental systems might, in fact, model the amplification and propagation of the first replicators in primordial environmental settings [57,351,354].…”
Section: Colonization Wavesmentioning
confidence: 99%
“…Chetverin and co-workers have introduced and studied RNA colonies that grew and propagated on gels or other solid media provided that RNA replicases and ribonucleoside triphosphates were present [351,377,378]. It has been explicitly noted that such experimental systems might, in fact, model the amplification and propagation of the first replicators in primordial environmental settings [57,351,354].…”
Section: Colonization Wavesmentioning
confidence: 99%
“…Amplification of small RQ RNAs is much faster: up to 10 10 copies are produced at room temperature within 10 min in a cell-free system comprised of purified Q␤ replicase and all four NTPs (3), and this is the absolute record of the rate of nucleic acid amplification. The high amplification rate allows single RQ RNA molecules to rapidly produce detectable molecular colonies if they are amplified in a gel (9,10).…”
mentioning
confidence: 99%
“…Selection experiments indicated that only a few of the initial diversity of 10 12 unique sequences of 50 -77 nt in length are replicable (4), demonstrating a very high degree of template specificity of the enzyme. Now, almost 40 years since its discovery (11), this specificity remains a mystery.…”
mentioning
confidence: 99%
“…Because acrylamide restricts the diffusion of the PCR amplification products, each single molecule included in the reaction produces a spherical colony of DNA, which we have termed polony (short for polymerase colony). A similar technology, the molecular colony technique, grows nucleic acid colonies in acrylamide using Q beta replicase or PCR [16,17]. Here we describe our progress in developing a protocol for sequencing polonies in parallel by performing repeated cycles of primer extension with fluorescent deoxynucleotides.…”
Section: Analytical Biochemistrymentioning
confidence: 99%